2021
DOI: 10.1002/ehf2.13220
|View full text |Cite
|
Sign up to set email alerts
|

Low‐fat hypocaloric diet reduces neprilysin in overweight and obese human subjects

Abstract: Aims Neprilysin (NEP), a zinc metallopeptidase, degrades a variety of bioactive peptides including natriuretic peptides terminating their biological action on arterial blood pressure and natriuresis. Pharmacological inhibition of NEP reduces mortality in patients with heart failure with reduced ejection fraction. Physiological interventions reducing NEP levels are unknown in humans. Because obesity leads to increased NEP levels and increases the risk for heart failure, we hypothesized that weight loss reduces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In the TONE trial, moderate weight loss decreased the need for antihypertensive therapy by approximately 30% in older hypertensive patients on a single antihypertensive drug [1469]. The BP-lowering effects of weight reduction achieved by dietary approaches are also supported by meta-analyses [1470], and evidence is available that loss of body weight reduces sympathetic activity [367], while reversing abnormalities in natriuretic peptide regulation [1471,1472]. Thus, lifestyle interventions aimed at reducing body weight are recommended in patients with obesity and hypertension through low caloric diets and increased physical activity.…”
Section: Hypertension and Other Selected Comorbiditiesmentioning
confidence: 99%
“…In the TONE trial, moderate weight loss decreased the need for antihypertensive therapy by approximately 30% in older hypertensive patients on a single antihypertensive drug [1469]. The BP-lowering effects of weight reduction achieved by dietary approaches are also supported by meta-analyses [1470], and evidence is available that loss of body weight reduces sympathetic activity [367], while reversing abnormalities in natriuretic peptide regulation [1471,1472]. Thus, lifestyle interventions aimed at reducing body weight are recommended in patients with obesity and hypertension through low caloric diets and increased physical activity.…”
Section: Hypertension and Other Selected Comorbiditiesmentioning
confidence: 99%
“…5 In the case of rs701109, patients with the alternative allele had signi cantly higher neprilysin protein levels, which might result in the promotion of amyloid-β degradation. 10,17 There are other factors that may have impacted our ndings of continental differences in dementiarelated AEs. Epidemiologic research on dementia and Alzheimer's disease suggests that the prevalence is higher in North America than in Asia, Africa, and Latin America.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Henke et al investigated how blood neprilysin concentrations were affected by a six-month weight-reduction diet leading to weight loss. The researchers showed a significant decrease in blood levels of this adipokine due to the dietary intervention in the low-fat diet group, which they did not find with the low-carbohydrate diet, despite comparable weight loss in both groups [27]. On this basis, it can be suggested that neprilysin concentrations depend more on the diet (which can lead to weight gain or loss) than on the subjects' weight.…”
Section: Adipokines and Anthropometric Parametersmentioning
confidence: 94%